FDA’s Proposed Rule for Pregnancy and Lactation Labeling: Improving maternal child health through well-informed medicine use - Feibus, Karen B. (Springer-Verlag, 2008)
For the US Food and Drug Administration (FDA), the May 29, 2008 publication of the Proposed Rule for Pregnancy and Lactation Labeling for Human Prescription Drug and Biological Products heralded both an end and a beginning. It marked an end to the labeling initiative process that produced the Proposed Rule and the beginning of FDA’s second-generation approach to labeling drugs and biologics for use during pregnancy, breastfeeding, and the childbearing years. These proposed changes reflect the extensive input and feedback FDA collected from clinicians and experts, and are designed to facilitate informed counseling about and prescribing of medicines for women who are pregnant, breastfeeding, or of childbearing potential. The prescription drug label is FDA’s communication tool—it is the place to clearly convey what is known about the safe and effective use of a drug in various populations. With development and implementation of the Physician Labeling Rule (PLR), FDA transformed the prescription drug label into a better communication tool in which information is better organized, clearly presented, and more easily located. The Proposed Rule for Pregnancy and Lactation Labeling is the final piece of PLR, creating a detailed and defined framework in which to present what is and is not known about the use of drugs during pregnancy and breastfeeding.